KENDALA PEMBELAJARAN SISTEM BERGELOMBANG DI SMP PAB 5 PATUMBAK 1 - M.Rizki Wijaya Tanjung; Munawir Pasaribu (Jurnal Masyarakat Indonesia (Jumas), 2022)
Teaching and learning activities in Indonesia during COVID-19 Pandemics are getting worse day by day due to the implementation of online schools from their respective homes and even face-to-face schools, but using the wave system is a big obstacle for teachers and guardians in general. With online schools, all teaching and learning activities should be delivered in totality. This also imposes distance learning (PJJ) which makes students' interest in learning decrease.